Flame-retardant polypropylene composite material and preparation method thereof

Through the synergistic effect of zinc-nickel bimetallic oxide catalyst and NOR 116 or GW-540, the problem of insufficient flame retardant performance of polypropylene materials is solved, and efficient flame retardant effect is achieved, achieving UL-94 V0 level and ultimate oxygen index improvement .

CN119192731AActive Publication Date: 2024-12-27SHAOXING XINGXIN CHEM +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411707009.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The flame retardant performance of existing polypropylene materials is insufficient, especially at a lower additive amount, piperazine pyrophosphate expanded flame retardant system does not have a flame retardant grade in polypropylene, and the traditional flame retardant additive amount is too high and the efficiency is low.

Method used

The zinc-nickel bimetal oxide catalyst is used to coordinate flame retardant, and ZnO and NiO are uniformly dispersed by co-precipitation method, combined with NOR 116 or GW-540 as flame retardant additives to improve the flame retardant performance of polypropylene.

Benefits of technology

The high flame retardant performance of polypropylene materials has been achieved, reaching the UL-94 V0 level, the limit oxygen index has been improved, the material has been converted into a flame retardant material, and the flame retardant performance has been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of compositions of high-molecular compounds, and relates to a flame-retardant high-molecular material, in particular to a flame-retardant polypropylene composite material and a preparation method thereof. The invention provides a flame-retardant polypropylene composite material. The flame-retardant polypropylene composite material is prepared from polypropylene, an intumescent flame retardant, a catalyst, a flame-retardant aid and a compatilizer, the flame retardant auxiliary agent is NOR 116 or GW-540; and the flame retardant auxiliary agent is a flame retardant. The catalyst is a zinc-nickel bimetallic oxide catalyst. The invention also provides a preparation method of the flame-retardant polypropylene composite material. The preparation method comprises the following steps: mixing polypropylene, the intumescent flame retardant, the catalyst, the flame-retardant aid and the compatilizer, and granulating. By adopting the method disclosed by the invention, the polypropylene composite material with high flame retardant property can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer compound compositions, relates to flame-retardant polymer materials, and specifically relates to a flame-retardant polypropylene composite material and a preparation method thereof. Background Art

[0002] Polypropylene (PP) is a polymer formed by the addition polymerization of propylene. It is a colorless, odorless, non-toxic, translucent solid substance with excellent physical, chemical and processing properties. Therefore, it is widely used in the fields of packaging materials, household goods, medical devices and automotive accessories. However, the limiting oxygen index of pure PP is only 17% to 18%, which is a flammable material. In addition, PP will produce a large number of molten droplets when burning, which can easily ignite surrounding objects, posing a huge safety hazard.

[0003] As flame retardant technology develops towards environmental protection, high efficiency, and smoke-free, halogen flame retardants are gradually replaced. As a rising star, piperazine pyrophosphate (PAPP) integrates flame retardant elements such as P, N, and C, and also has the functions of carbon source, gas source, and acid source. It has extremely high light stability and thermal stability. The decomposition temperature exceeds 300°C when the dosage is 5%, which is suitable for the processing temperature of most resins. Preliminary research results show that compared with the traditional intumescent flame retardant with ammonium polyphosphate (APP) as the core, the piperazine pyrophosphate system has better flame retardant effect, and its addition amount is significantly reduced when the same flame retardant level is achieved, and the heat stability and water precipitation resistance are significantly improved. However, due to the insufficient carbonization ability of the PAPP system, the PAPP intumescent flame retardant system also has no flame retardant grade in polypropylene at a lower addition amount.

[0004] Patent CN117430891A discloses flame retardant polypropylene by adding phosphorus-nitrogen expansion system, and introduces magnesium synergist, but the flame retardant effect is general, and at least 24 parts of phosphorus-nitrogen flame retardant must be added to pass V0 level. Patent CN117700879A discloses nickel-based bimetallic catalyst synergistically catalyzing inorganic flame-retardant polypropylene carbonization flame-retardant composite material and its preparation method, with nickel-based as the main catalyst, Al, Mg, and Co as the second metal, and activated carbon synergistically acidified by nickel-based bimetallic catalyst to synergistically flame retard the inorganic flame-retardant polypropylene system carbonization flame-retardant composite material. Although the amount of inorganic flame retardant added is reduced compared with previous technologies, the total amount of flame retardant added exceeds 50% of the system, and the flame retardant efficiency is still very low.

[0005] NOR 116 is an N-alkoxy hindered amine flame retardant and light stabilizer produced by BASF. As a flame retardant alone, it shows V2 flame retardant effect in polyolefin fibers, non-woven fabrics and films. It has no flame retardant effect when used alone in thicker plastics. Patent CN116218077A discloses a halogen-free flame retardant masterbatch, a halogen-free flame retardant composite material, and its preparation method and application. NOR 116 is used as a light stabilizer in combination with a metal hydroxide flame retardant and a phosphorus flame retardant. The system can only reach V2 level and has low flame retardant efficiency.

[0006] GW-540 is a hindered amine light stabilizer that inhibits or slows down the degradation of polymer materials due to photooxidation. Patent CN116285407A discloses a high-fluidity tea residue / polypropylene composite material and its preparation method, which introduces GW-540 as a light stabilizer to mainly solve the aging and degradation problem during material processing. At present, GW-540 is mainly used as a light stabilizer, and there is little research on its use as a flame retardant additive. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a flame retardant polypropylene composite material with high flame retardancy and a preparation method thereof.

[0008] In order to solve the above technical problems, the present invention provides a flame-retardant polypropylene composite material (zinc-nickel bimetallic oxide catalytic synergistic flame-retardant polypropylene composite material), which is composed of 80-85 parts of polypropylene, 14.5-18.7 parts of intumescent flame retardant, 0.2-0.5 parts of catalyst, 0.1-0.5 parts of flame retardant additive and 0.1-0.5 parts of compatibilizer in parts by weight; The flame retardant additive is NOR 116 or GW-540; The catalyst is a zinc-nickel bimetallic oxide catalyst, and the zinc-nickel bimetallic oxide catalyst is Zn x Ni y O, x is any one between 0.7 and 0.9, y is any one between 0.1 and 0.3; and x+y=1.

[0009] As an improvement of the flame retardant polypropylene composite material of the present invention: x is 0.8, and y is 0.2.

[0010] As a further improvement of the flame-retardant polypropylene composite material of the present invention: the intumescent flame retardant is composed of a main flame retardant and a secondary flame retardant, and the mass ratio of the main flame retardant to the secondary flame retardant is 2 to 4:1; the main flame retardant is piperazine pyrophosphate (PAPP), and the secondary flame retardant is any one of melamine polyphosphate (MPP), aluminum hypophosphite (HDP), and diethyl aluminum phosphite (ADP).

[0011] As a further improvement of the flame-retardant polypropylene composite material of the present invention: the compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene.

[0012] As a further improvement of the flame-retardant polypropylene composite material of the present invention, the preparation method of the zinc-nickel bimetallic oxide catalyst is: Under mechanical stirring, zinc nitrate hexahydrate and nickel nitrate hexahydrate are dissolved in distilled water to obtain a bimetallic solution; the mass ratio of zinc in the zinc nitrate hexahydrate to nickel in the nickel nitrate hexahydrate is 7-9:1-3; Under stirring, the bimetallic solution is reacted at 80±10℃ for 2±0.5 h, and the pH of the reaction system is controlled to be 8~9 during the reaction (it can be controlled by dropping a 10% sodium carbonate solution); After the reaction is completed, ageing (stationary aging) is carried out at 80±10°C for 1±0.2h, followed by filtration. The filter cake is washed with deionized water (washed several times until the pH of the washing liquid is neutral), and then dried (force drying at 100~120°C for 4~6h), and then calcined at 450~550°C for 3.5~4.5h (calcination can be carried out in a muffle furnace). After grinding, a zinc-nickel bimetallic oxide catalyst is obtained.

[0013] Note: Generally speaking, 200 ml of distilled water is used to dissolve every 7-50 g of nickel nitrate hexahydrate.

[0014] The present invention also provides a method for preparing the flame retardant polypropylene composite material as described above, comprising the following steps: (1) Weigh polypropylene, intumescent flame retardant, catalyst, flame retardant additive and compatibilizer by weight and premix them in a mixer at 80±10℃ for 5±1 min; the premixing speed is 300±50 r / min; (2) The mixed material obtained in step (1) is melted and sheared and mixed by a twin-screw extruder, and then extruded into granules. The extrusion temperature is 165-210 °C, the rotation speed is 450±50 r / min, and the feed speed is 30±3 r / min.

[0015] NOR 116 and GW-540 are mainly used in plastics for anti-aging. The present invention finds that they can capture free radicals generated by the photo-oxidation and combustion degradation of polymers, thereby interrupting the chain reaction in the combustion process and achieving a gas phase flame retardant effect. Therefore, in the specific formulation of the present invention, they can be used as flame retardant additives and have an unexpected flame retardant effect.

[0016] The present invention uses an expansion flame retardant system mainly composed of PAPP, supplemented by MPP, HDP and ADP, and the flame retardant efficiency is significantly improved compared with inorganic flame retardants and traditional APP systems. In view of the insufficient carbonization ability of the PAPP system and the fact that the PAPP expansion flame retardant system also has no problem of flame retardant grade in polypropylene at a lower addition amount, the present invention uniformly disperses ZnO and NiO together by a coprecipitation method to obtain a zinc-nickel bimetallic oxide catalyst; Zn and Ni are in a specific ratio, and the two synergistically catalyze the dehydrogenation of the PAPP system and polypropylene to form a high-quality carbon layer to isolate heat, thereby preventing the polypropylene material from being ignited. However, since polypropylene conducts heat very quickly, when the strip is ignited, the polypropylene will quickly degrade due to heat, resulting in the zinc-nickel bimetallic oxide catalyst not having time to play its catalytic carbonization role. Based on this, the present invention further adds NOR116 or GW-540 with gas phase flame retardant effect. When the sample is just ignited, NOR 116 or GW-540 can quickly degrade and capture active free radicals in the air, interrupt the chain decomposition reaction, exert the gas phase flame retardant effect, and buy time for catalytic carbonization.

[0017] In the present invention, the compatibilizer serves to improve the compatibility and dispersibility of the intumescent flame retardant and the catalyst with the polypropylene, thereby enhancing the mechanical properties of the mixed material.

[0018] In summary, the present invention uses the intumescent flame retardant, the zinc-nickel bimetallic oxide catalyst and NOR 116 or GW-540 to complement each other to synergistically flame retard polypropylene, thereby obtaining a polypropylene composite material with high flame retardancy. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0020] The raw materials used in the present invention are all commonly used raw materials in the art. For example: Polypropylene was purchased from Baling Petrochemical, piperazine pyrophosphate was produced by Shaoxing Xingxin New Materials Co., Ltd.; ammonium polyphosphate, melamine polyphosphate, aluminum hypophosphite, aluminum diethylphosphinate and magnesium hydroxide were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; zinc nitrate hexahydrate, nickel nitrate hexahydrate, zinc oxide and nickel oxide were purchased from Shanghai MacLean Biochemical Technology Co., Ltd., NOR 116 (BASF flame retardant NOR116, Germany) was purchased from Dafa Chemical Co., Ltd., GW-540 (light stabilizer GW-540) and UV-770 (light stabilizer UV-770) were purchased from Shanghai Yihe Biotechnology Co., Ltd.; maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0021] 1. Preparation of zinc-nickel bimetallic oxide catalyst: Example 1: 51.17 g of zinc nitrate hexahydrate (containing 11.18 g of zinc) and 23.72 g of nickel nitrate hexahydrate (containing 4.79 g of nickel) were completely dissolved in 200 ml of distilled water under mechanical stirring to obtain a bimetallic solution; Under stirring conditions, the bimetallic solution was reacted at 80°C for 2 h, and the pH of the reaction system was controlled to be 8 during the reaction (which can be controlled by dropping a 10% sodium carbonate solution); After the reaction, the mixture was aged at 80°C for 1 h, then filtered, and the filter cake was washed with deionized water several times until the pH was neutral, then dried at 110°C for 5 h, and finally calcined in a muffle furnace at 500°C for 4 h. After grinding, it was passed through a 200-mesh sieve to obtain a zinc-nickel bimetallic oxide catalyst, denoted as Zn 0.7 Ni 0.3 O.

[0022] Example 2: 58.48 g of zinc nitrate hexahydrate (containing 12.76 g of zinc) and 15.80 g of nickel nitrate hexahydrate (containing 3.19 g of nickel) were completely dissolved in 200 ml of distilled water under mechanical stirring to obtain a bimetallic solution; Under stirring conditions, the bimetallic solution was reacted at 80°C for 2 h, and the pH of the reaction system was controlled to be 8.5 during the reaction (which can be controlled by dropping a 10% sodium carbonate solution); After the reaction, the mixture was aged at 80°C for 1 hour, and then filtered. The filter cake was washed with deionized water several times until the pH was neutral, and then dried at 110°C for 5 hours. Finally, it was calcined in a muffle furnace at 500°C for 4 hours. After grinding, it was passed through a 200-mesh sieve to obtain a zinc-nickel bimetallic oxide catalyst, which was recorded as Zn 0.8 Ni 0.2 O.

[0023] Example 3: 65.79 g of zinc nitrate hexahydrate (containing 14.37 g of zinc) and 7.92 g of nickel nitrate hexahydrate (containing 1.6 g of nickel) were completely dissolved in 200 ml of distilled water under mechanical stirring to obtain a bimetallic solution; Under stirring conditions, the bimetallic solution was reacted at 80°C for 2 h, and the pH of the reaction system was controlled to be 9 during the reaction (which can be controlled by dropping a 10% sodium carbonate solution); After the reaction, the mixture was aged at 80°C for 1 hour, and then filtered. The filter cake was washed with deionized water several times until the pH was neutral, and then dried at 110°C for 5 hours. Finally, it was calcined in a muffle furnace at 500°C for 4 hours. After grinding, it was passed through a 200-mesh sieve to obtain a zinc-nickel bimetallic oxide catalyst, which was recorded as Zn 0.9 Ni 0.1 O.

[0024] Example 4: 29.24 g of zinc nitrate hexahydrate (containing 6.39 g of zinc) and 47.46 g of nickel nitrate hexahydrate (containing 9.58 g of nickel) were completely dissolved in 200 ml of distilled water under mechanical stirring to obtain a bimetallic solution; Under stirring conditions, the bimetallic solution was reacted at 80°C for 2 h, and the pH of the reaction system was controlled to be 8 during the reaction (which can be controlled by dropping a 10% sodium carbonate solution); After the reaction, the mixture was aged at 80°C for 1 hour, and then filtered. The filter cake was washed with deionized water several times until the pH was neutral, and then dried at 110°C for 5 hours. Finally, it was calcined in a muffle furnace at 500°C for 4 hours. After grinding, it was passed through a 200-mesh sieve to obtain a zinc-nickel bimetallic oxide catalyst, which was recorded as Zn 0.4 Ni 0.6 O.

[0025] Example 5: 36.55 g of zinc nitrate hexahydrate (containing 7.98 g of zinc) and 39.54 g of nickel nitrate hexahydrate (containing 7.98 g of nickel) were completely dissolved in 200 ml of distilled water under mechanical stirring to obtain a bimetallic solution; Under stirring conditions, the bimetallic solution was reacted at 80°C for 2 h, and the pH of the reaction system was controlled to be 8 during the reaction (which can be controlled by dropping a 10% sodium carbonate solution); After the reaction, the mixture was aged at 80°C for 1 hour, and then filtered. The filter cake was washed with deionized water several times until the pH was neutral, and then dried at 110°C for 5 hours. Finally, it was calcined in a muffle furnace at 500°C for 4 hours, and then ground and passed through a 200-mesh sieve to obtain a zinc-nickel bimetallic oxide catalyst, which was recorded as Zn 0.5 Ni 0.5 O.

[0026] Example 6: 43.86 g of zinc nitrate hexahydrate (containing 9.58 g of zinc) and 31.64 g of nickel nitrate hexahydrate (containing 6.39 g of nickel) were completely dissolved in 200 ml of distilled water under mechanical stirring to obtain a bimetallic solution; Under stirring conditions, the bimetallic solution was reacted at 80°C for 2 h, and the pH of the reaction system was controlled to be 8 during the reaction (which can be controlled by dropping a 10% sodium carbonate solution); After the reaction, the mixture was aged at 80°C for 1 hour, and then filtered. The filter cake was washed with deionized water several times until the pH was neutral, and then dried at 110°C for 5 hours. Finally, it was calcined in a muffle furnace at 500°C for 4 hours. After grinding, it was passed through a 200-mesh sieve to obtain a zinc-nickel bimetallic oxide catalyst, which was recorded as Zn 0.6 Ni 0.4 O.

[0027] 2. Preparation of flame-retardant polypropylene composite materials (zinc-nickel bimetallic oxide catalytic synergistic flame-retardant polypropylene composite materials): The following parts are by weight.

[0028] Example 1: A zinc-nickel bimetallic oxide catalyzed synergistic flame-retardant polypropylene composite material, the formula of which is as follows: 85 parts of polypropylene, 14.5 parts of intumescent flame retardant, 0.2 parts of zinc-nickel bimetallic oxide catalyst, 0.1 parts of flame retardant additive, and 0.2 parts of compatibilizer; The intumescent flame retardant is composed of a primary flame retardant, piperazine pyrophosphate (PAPP), and a secondary flame retardant, melamine polyphosphate (MPP), with a mass ratio of PAPP / MPP=2:1; The zinc-nickel bimetallic oxide catalyst is Zn 0.7 Ni 0.3 O; The flame retardant additive is NOR 116; The compatibilizer is maleic anhydride grafted polypropylene.

[0029] The preparation method is to carry out the following steps in sequence: 1) According to the formula, weigh polypropylene, intumescent flame retardant, zinc-nickel bimetallic oxide catalyst, flame retardant additive and compatibilizer, and premix them in a high-speed mixer at a high speed (speed of 300 r / min). The premixing temperature is 80 °C and the premixing time is 5 minutes. 2) The mixed material obtained in step 1) is melted and sheared and mixed by a twin-screw extruder, and then extruded and granulated. The extrusion temperature is 165-210°C, the rotation speed is 450 r / min, and the feed speed is 30 r / min. The obtained particle size is about 2-3 mm.

[0030] Example 2 to Example 11, relative to Example 1, the formula is changed, the formula is specifically as shown in Table 1, in which: the mass ratio of PAPP / MPP is 2:1, the mass ratio of PAPP / HDP is 3:1, and the mass ratio of PAPP / ADP is 4:1. The preparation method is the same as that of Example 1.

[0031] Table 1 Components of flame retardant polypropylene composition

[0032] Comparative Example 1 is a blank comparative example, that is, pure polypropylene; the difference from Example 1 is that no intumescent flame retardant, zinc-nickel bimetallic oxide catalyst, flame retardant additive and compatibilizer are added.

[0033] Comparative Example 2: The difference from Example 1 is that no zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O, i.e., Zn0.7 Ni 0.3 The dosage of O is 0; the rest is the same as in Example 1.

[0034] Comparative Example 3: The difference from Example 1 is that the zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O is replaced with ZnO / NiO of equal weight; the rest is the same as in Example 1.

[0035] ZnO and NiO are mixed according to a mass ratio of Zn:Ni=7:3 to obtain corresponding ZnO / NiO.

[0036] Comparative Example 4: The difference from Example 1 is that the zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O is replaced with an equal amount of ZnO; the rest is the same as in Example 1.

[0037] Comparative Example 5: The difference from Example 1 is that the zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O is replaced by an equal amount of NiO; the rest is the same as in Example 1.

[0038] Comparative Example 6: The difference from Example 1 is that the zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O is replaced by an equal amount of Zn 0.4 Ni 0.6 O; the rest is the same as Example 1.

[0039] Comparative Example 7: The difference from Example 1 is that the zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O is replaced by an equal amount of Zn 0.5 Ni 0.5 O; the rest is the same as Example 1.

[0040] Comparative Example 8: The difference from Example 1 is that the zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O is replaced by an equal amount of Zn 0.6 Ni 0.4 O; the rest is the same as Example 1.

[0041] Comparative Example 9: The difference from Example 1 is that the flame retardant additive NOR 116 is not added; the rest is the same as Example 1.

[0042] Comparative Example 10: The difference from Example 4 is that the flame retardant additive GW-540 is not added; the rest is the same as Example 4.

[0043] Comparative Example 11: The difference from Example 1 is that the amount of the flame retardant additive NOR 116 is increased from 0.1 part to 0.6 part; the rest is the same as Example 1.

[0044] Comparative Example 12: The difference from Example 4 is that the amount of flame retardant additive GW-540 is increased from 0.2 parts to 0.6 parts; the rest is the same as Example 4.

[0045] Comparative Example 13: The difference from Example 4 is that the flame retardant additive GW-540 is replaced with the commonly used light stabilizer UV-770 on the market; the rest is the same as Example 4.

[0046] Comparative Example 14: The difference from Example 1 is that the intumescent flame retardant PAPP / MPP is replaced with an equal amount of inorganic flame retardant magnesium hydroxide; the rest is the same as Example 1.

[0047] Comparative Example 15: The difference from Example 1 is that the intumescent flame retardant PAPP / MPP is replaced with an equal mass portion of the PAPP / APP system. That is, the secondary flame retardant in Example 1 is changed from "melamine polyphosphate (MPP)" to "ammonium polyphosphate (APP)", and the rest is the same as Example 1.

[0048] Comparative Example 16: The difference from Example 1 is that the mass ratio of PAPP / MPP is changed from "2:1" to "1:1", and the rest is the same as Example 1.

[0049] Experimental and performance evaluation of polypropylene composites 1. The flame retardant performance test conditions and standards are as follows: UL-94 vertical burning specimen size: 130 × 13 × 3.2 mm 3 Test standard: ASTM D3801; LO Index strip size: 100 × 6.5 × 3.2 mm 3 Test standard: ASTM 2863; The peak burning rate (pk-HRR) and total heat of combustion (THR) are the parameters that best represent the flame retardancy of the material in the cone calorimetry test. The higher the pk-HRR and THR values, the more flammable the material is and the higher the risk of fire. The sample size for the test is: 100 × 100 × 3.2 mm 3 , the test standard is: ISO 5660.

[0050] 2. Mechanical properties test conditions and standards are as follows: The specimen size of the tensile properties is 2 mm × 35 mm × 0.8 mm, the tensile rate is 20 mm / min, and the test standard is ASTM D882.

[0051] The specimen size for bending performance is 80 mm × 10 mm × 4 mm, and the test standard is GB / T 1040.1-2006.

[0052] The specimen size for notched impact performance is 80 mm × 10 mm × 4 mm, and a 1 J pendulum is used for impact. The test standard is ISO179-1:98.

[0053] The results are shown in Table 2 below.

[0054] Table 2 Flame retardant properties and mechanical properties

[0055] From the test results in Table 2, it can be found that pure polypropylene has no flame retardant grade, while Examples 1 to 11 of the present invention can all pass the UL-94 V0 grade test, and the limiting oxygen index is also increased from 17.8 vol% of pure polypropylene to more than 30 vol%, changing from a flammable material to a flame retardant material, and the flame retardant performance is greatly improved.

[0056] From the comparison between Comparative Example 2 and Example 1, when no zinc-nickel bimetallic oxide catalyst Zn 0.7 Ni 0.3 O, the carbonization ability of the specimen is too weak to protect the substrate to achieve the heat insulation effect, so that it burns to the fixture during the second ignition and has no flame retardant grade. 0.7 Ni 0.3 After replacing ZnO / NiO with a ZnO / NiO mixture of the same mass ratio (Comparative Example 3), there is still no flame retardant grade, indicating that the catalytic carbonization ability of the ZnO / NiO mixture simply blended on the strips is very weak, so that the flame retardant effect cannot be improved. The zinc-nickel bimetallic oxide catalyst obtained by the coprecipitation method of the present invention can greatly improve the catalytic carbonization effect on the strips, thereby enhancing the flame retardant properties of the polypropylene composite material. Furthermore, by comparing Comparative Example 4 and Comparative Example 5 with Example 1, it is found that the polypropylene composite material obtained by using ZnO or NiO alone still has no flame retardant grade. By comparing Comparative Example 6, Comparative Example 7, Comparative Example 8 with Example 1, it can be seen that the mass ratio of zinc and nickel is also a key factor. Only when the zinc content is between 70% and 90%, there is an obvious flame retardant effect and reaches the V0 level. Among them, from Examples 1, 2 and 3, the catalyst used in Example 2 is Zn 0.8 Ni 0.2 O, that is, when the mass ratio of zinc to nickel is 8:2, the flame retardant properties of the specimens are higher than those of Zn 0.7 Ni 0.3 O and Zn 0.9 Ni 0.1 O corresponds to the performance of the spline, which is the optimal ratio of zinc and nickel.

[0057] From Comparative Examples 9 and 10, it was found that when no flame retardant additive was added, the strips also had no flame retardant grade. The addition of flame retardant additives buys time for the catalytic carbonization of the catalyst, so the flame retardant effect has been significantly improved. Further, through Comparative Examples 11 and 12, it was found that when the amount of flame retardant additives (NOR 116 or GW-540) added exceeded 0.5 parts, it could only reach the V2 grade. This is because NOR 116 and GW-540 can not only capture active free radicals, but also act as initiators to promote the degradation of polypropylene. When the amount of flame retardant additives (NOR 116 or GW-540) added is low, they mainly play a role in quenching free radicals and exert a flame retardant effect, but when the amount added is too high, they mainly act as initiators, promote the degradation of polypropylene, cause the generation of molten droplets, and ignite the absorbent cotton. Comparative Example 13 shows that not all light stabilizers have such flame retardant effect. The reason why the addition of light stabilizers NOR 116 and GW-540 significantly improves the flame retardant effect of polypropylene is that their decomposition temperatures match the decomposition temperature of polypropylene and both have excellent gas phase flame retardant effect.

[0058] From the comparison between Comparative Example 14 and Example 1, after replacing the intumescent flame retardant PAPP / MPP with an equal amount of inorganic flame retardant magnesium hydroxide, the specimen has no flame retardant grade, and the heat release rate increases to 525 KW / m 2 , the flame retardant performance is greatly reduced. This is because magnesium hydroxide needs to be added in an amount of more than 40% to have a significant flame retardant effect.

[0059] Comparative Examples 15 and 16 both show no flame retardancy.

[0060] In summary, the present invention provides a flame-retardant polypropylene with excellent comprehensive performance and a preparation method thereof, and also provides a broader space for the application of polypropylene.

[0061] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. Flame retardant polypropylene composite material, characterized by: According to weight parts, it is composed of 80-85 parts of polypropylene, 14.5-18.7 parts of intumescent flame retardant, 0.2-0.5 parts of catalyst, 0.1-0.5 parts of flame retardant additive and 0.1-0.5 parts of compatibilizer; The flame retardant additive is NOR 116 or GW-540; The catalyst is a zinc-nickel bimetallic oxide catalyst, and the zinc-nickel bimetallic oxide catalyst is Zn x Ni y O, x is any one between 0.7 and 0.9, y is any one between 0.1 and 0.3; and x+y=1.

2. The flame retardant polypropylene composite material according to claim 1, characterized in that: x is 0.8 and y is 0.

2.

3. The flame retardant polypropylene composite material according to claim 1 or 2, characterized in that: The intumescent flame retardant is composed of a main flame retardant and a secondary flame retardant, with the mass ratio of the main flame retardant to the secondary flame retardant being 2 to 4:1; The main flame retardant is piperazine pyrophosphate, and the secondary flame retardant is any one of melamine polyphosphate, aluminum hypophosphite, and aluminum diethylphosphinate.

4. The flame retardant polypropylene composite material according to claim 3, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene.

5. The flame retardant polypropylene composite material according to claim 4, characterized in that: The preparation method of the zinc-nickel bimetallic oxide catalyst is: Under stirring, dissolving zinc nitrate hexahydrate and nickel nitrate hexahydrate in distilled water to obtain a bimetallic solution; the mass ratio of zinc in the zinc nitrate hexahydrate to nickel in the nickel nitrate hexahydrate is 7-9:1-3; Under stirring, the bimetallic solution was reacted at 80±10℃ for 2±0.5 h, and the pH of the reaction system was controlled to be 8~9 during the reaction; After the reaction is completed, the mixture is aged at 80±10°C for 1±0.2h and then filtered. The filter cake is washed with deionized water and then dried. The mixture is then calcined at 450~550°C for 3.5~4.5h and ground to obtain a zinc-nickel bimetallic oxide catalyst.

6. The method for preparing the flame retardant polypropylene composite material according to any one of claims 1 to 5, characterized in that The following steps are involved: (1) Weigh polypropylene, intumescent flame retardant, catalyst, flame retardant additive and compatibilizer according to weight, and premix them in a mixer at 80±10℃ for 5±1 min; the premixing speed is 300±50 r / min; (2) The mixed material obtained in step (1) is melted and sheared and mixed by a twin-screw extruder, and then extruded into granules. The extrusion temperature is 165-210°C, the rotation speed is 450±50 r / min, and the feed speed is 30±3 r / min.

Citation Information

Patent Citations

  • Halogen-free flame-retardant master batch, halogen-free flame-retardant composite material and preparation method and application of halogen-free flame-retardant master batch

    CN116218077A

  • High-fluidity tea residue / polypropylene composite material and preparation method thereof

    CN116285407A

  • Flame retardant polypropylene material with good light stability and preparation method thereof

    CN108659339A

  • Preparation method of carbon cloth loaded zinc nickel double metal hydroxide water splitting catalyst

    CN109174104A

  • High strength flame retardant polypropylene material

    CN109762253A